The water content of recurring slope lineae on Mars - Christopher S. Edwards; Sylvain Piqueux (Geophysical Research Letters)
Abstract Observations of recurring slope lineae (RSL) from the High‐Resolution Imaging Science Experiment have been interpreted as present‐day, seasonally variable liquid water flows; however, orbital spectroscopy has not confirmed the presence of liquid H2O, only hydrated salts. Thermal Emission Imaging System (THEMIS) temperature data and a numerical heat transfer model definitively constrain the amount of water associated with RSL. Surface temperature differences between RSL‐bearing and dry RSL‐free terrains are consistent with no water associated with RSL and, based on measurement uncertainties, limit the water content of RSL to at most 0.5–3 wt %. In addition, distinct high thermal inertia regolith signatures expected with crust‐forming evaporitic salt deposits from cyclical briny water flows are not observed, indicating low water salinity (if any) and/or low enough volumes to prevent their formation. Alternatively, observed salts may be preexisting in soils at low abundances (i.e., near or below detection limits) and largely immobile. These RSL‐rich surfaces experience ~100 K diurnal temperature oscillations, possible freeze/thaw cycles and/or complete evaporation on time scales that challenge their habitability potential. The unique surface temperature measurements provided by THEMIS are consistent with a dry RSL hypothesis or at least significantly limit the water content of Martian RSL.